Digital Trade Finance Transformation and Sustainable Marketing Strategies: A Literature Review - Indrianti, Marini Astari; Nurdin, Asep; Perdhana, Mirwan Surya (Economic and Business Horizon, 2025)
Digital transformation is reshaping the banking sector, particularly in trade finance, improving operational efficiency and providing better solutions for international transactions. Bank Rakyat Indonesia (BRI) developed the "Qlola by BRI" platform to streamline trade finance services, though challenges like low digital literacy, cybersecurity risks, and resistance to change persist. This study employs a literature review methodology to explore the integration of digital transformation and sustainable marketing strategies in BRI’s trade finance operations. By synthesizing existing research, the study examines BRI’s strategies in addressing these challenges and analyzes customer perceptions of digital platforms using the Technology Acceptance Model (TAM). The findings suggest that perceived ease of use and perceived usefulness are key factors in adopting digital solutions. Additionally, the research explores how integrating sustainable marketing strategies with digital efforts can enhance customer experience and foster long-term business growth. Insights from the review provide recommendations for financial institutions and policymakers to overcome barriers to digital adoption and implement effective sustainable marketing practices.